Perception and Attitude towards Electronic Cigarettes among Rural Thai Young Adults - Songsin, Niwat; Wannapaschaiyong, Prakasit; Loylib, Pastsawut; Dampueak, Warodom; Kingkaew, Wanwimon Mekwimon; Siladlao, Sureewan; Somporn, Kanokporn (Siriraj Medical Journal, 2024)
Objective: This study examined perceptions and attitudes toward electronic cigarettes (e-cigarettes) among young adults aged 15-20 years in Samut Songkhram Province, Thailand, and their relationship. Materials and Methods: A descriptive cross-sectional study was conducted between July and October 2023. The study included 328 young adults aged 15-20 selected from an educational institution in Samut Songkhram Province using simple random sampling. Data were collected using a self-administered questionnaire and analyzed using descriptive statistics and Pearson’s correlation coefficient. Results: The participants had a good level of knowledge about e-cigarettes. They exhibited a positive attitude towards electronic cigarettes regarding health aspects (M=3.05, SD=0.97) and a positive attitude towards the legal dimensions of e-cigarettes (M=3.12, SD=0.80). However, no statistically significant correlation was found between the perception of e-cigarettes and health-related attitudes toward them (r=0.013, p=0.820). On the other hand, there was a statistically significant positive correlation between the perception of e-cigarettes and legally oriented attitudes (r=0.192, p<0.001). Furthermore, a borderline positive correlation emerged between the perception of electronic cigarettes and the general attitudes toward them (r=0.102, p=0.065). Conclusion: Young adults in rural Thailand have a good knowledge of e-cigarettes. However, they exhibit positive attitudes towards the health aspects and legal dimensions of e-cigarettes. Moreover, no significant relationship exists between perceptions and health-related attitudes. These insights emphasize the need for targeted strategies to address misperceptions and raise awareness about the health risks of e-cigarette use among rural youth.